DISTRIBUSI PENDAPATAN DAN PEMENUHAN KEBUTUHAN DALAM EKONOMI ISLAM - Eli Suryani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2010)
An income distribution in Islam uses an assumption that everything which is either consumed or produced must not been contained by riba also get been not contamined by an obligation to pay zakat for a consumer and producer. At the other hand, when we examine further, accord to the context of Islam, the distribution put in front an assumption that a measurement is not based on the property only, but also based on the distribution of the humanity potential use. So that, the best way used in Islam (perceiving capitalism and social system) is handling a principle of a must for producing more also the property distribution. This aims if the property circulation will be increasing for finally, so that it will give an implication for a fair distribution between such society levels. Thus, hopefully the property will be spreading out to all communities.